EFFECT OF PLANTING METHODS ON PERFORMANCE OF ONION VARIETIES UNDER COLD DESERT CONDITIONS - M. S. KANWAR,; AKBAR, P. ISHFAQ (The Bioscan, 2013)
A study was conducted at Research Farm of High Mountain Arid Agriculture Research Institute (SKUAST-K), Stakna, Leh to investigate the impact of three planting methods (Flat bed, Middle of Ridge, Both sides of Ridge) on the performance of four onion varieties in Split plot design with three replications. Flat bed system produced statistically highest net bulb weight (66.00g), bulb diameter (51.33mm) and yield per ha (440.2 qt). Net bulb weight, diameter and yield per ha of onion hybrid Rosy was highest but at par with Local Red and Nasik Red. It can be concluded that planting on flat land is best method for onion production in cold desert conditions.